Virtual teams - Beyerlein, Michael Martin; Johnson, Douglas A.; Beyerlein, Susan T. (Emerald, 2001)
Effective knowledge work depends on bringing people together to form a team with the right mix of expertise for the project or problem on hand. Increasingly, that mix can only be created by finding people who are geographically dispersed across sites of the company or across several companies. These virtual teams typically work by linking through electronic tools, such as the telephone, fax, email, NetMeeting, Lotus Notes, and other web-based communication systems. Recent research suggests that these teams have all of the challenges of face-to-face teams in addition to others, such as the limitations of technology, cultural differences, and multiple supervisors. The papers included in this volume identify some of the problems and some of the solutions to these kinds of problems, but most importantly, in a dynamic field such as virtual teams, the papers provide a framework for thinking about such problems and a collection of ideas that can form a foundation for advancing both research and practice in the field. Much of the literature on virtual teams focuses on the technology. The technology is an enabler, but it does not seem to have advanced far enough to make electronic communications as effective as face-to-face meetings. Like other teams, virtual teams consist of human beings and they have interpersonal and identity needs that must be met to optimize their ability to work and to collaborate. So, issues such as member solidarity, cooperation and unity of actions and values become special concerns. Such issues are addressed in this volume with the hope that this work will provide a foundation for moving ahead in this field toward more effective virtual teams.
Keywords: Teams in the workplace -- Data processing.; Personnel management.; elektronické knihy; electronic books